A survey of marine turtles found in Mayo Bay, Davao Oriental, Philippines - Lea Jimenez; Marlo Khen Inabiogan (Davao Research Journal)
Marine turtles are enlisted as critically endangered marine animals vulnerable to extinction. In Mayo Bay, Davao Oriental, the data on marine turtles' status is deficient. Land-based monitoring from 2014 to 2016 was dedicated to filling in the gaps in the knowledge and status of marine turtles in Mayo Bay. Four species, namely, Chelonia mydas, Eretmochelys imbricata, Lepidochelys olivacea, and Dermochelys coriacea, were identified as being present in the bay. Commonly sighted species were Chelonia mydas (n = 121), and the most numbered species accounted for stranding incidences (n = 9), generally due to by-catch using hook and line. Nesting activities recorded Lepidochelys olivacea as the prominent nester, with a total of 5,926 eggs laid and 4,956 eggs hatched and released with a hatching percentage of 84.03%. Chelonia mydas was observed to nest previously in 2014; however, it was found to be inactive after nesting in 2015 and 2016. Mayo Bay is found to be home to four species of marine turtles, although common challenges in conservation efforts are stranding incidences, beach encroachment, and intensive lighting due to resorts in the area. An intensive education campaign drive should be done, and the institutionalization of the protection of marine turtles should also be considered.